IN VITRO GERMINATION AND ITS SUBSEQUENT GROWTH OF AN ORCHID OF Vanda tricolor Lindl. var. suavis FROM BALI ON COMPLEX ADDITIVES ENRICHED MEDIUM - Dwiyani, Rindang; Yuswanti, Hestin; Darmawati, Ida Ayu Putri; Suada, Ketut; Mayadewi, Ni Nyoman Ari (AGRIVITA, Journal of Agricultural Science, 2015)
Vanda tricolor Lindl. var. suavis is an Indonesian wild orchid that has been rare in nature,  so it needs attention to take care and conserve them.  The objective of the research was to investigate the effect of coconut water and / or tomato juice on the growth of protocorm of V. tricolor Lindl. var suavis from Bali grown in vitro. The experiment was laid out in the factorial design, with two factors (coconut water/CW and tomato juice/TJ), each contained three concentration (CW: 0, 100, and 200 cc L-1; TJ: 0, 100 and 200 g L-1) resulted in nine combination of treatments and replicated four times.  The results showed that tomato juice with concentration of 100 gL-1 or 200 gL-1 promotes growth of protocorms of Vanda tricolor Lindl. var. suavis from Bali regardless the presence of  coconut water. Keywords: coconut water, in-vitro, protocorms, tomato juice, Vanda tricolor